Maqasid al-Shari’a and Contemporary Reformist Muslim Thought
XIII, 270 p.
Keywords: It is the first study which comprehensively, systematically and critically examines the role and usefulness of the concept of Maqasid al-Shari'a (higher Objectives of Islamic Law) in contemporary Muslim reformist thought in relation to number of specific issues pertaining to Islamic legal philosophy, law, ethics and the socio-political sphere.